Adhesion, Stretching, and Electrical Charge Assessment of Dermatan Sulfate Molecules by Colloidal Probes - Melo-Hurtado, F; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Caballero-Alvial, L; Gonzalez-Lagos, R (2012)
Electrical and mechanical properties of dermatan sulfate (DS) molecules are studied in an aqueous environment as a function of pH. DS molecules linked at various points distributed on the surface of mica previously silanizated along with a suitable functionalized microsphere, attached to the cantilever of an atomic force microscope (AFM), provided suitable surfaces for testing interactions through the colloidal probe methodology. The repulsive force between the surfaces indicated that the charge of DS increases with pH as a result of the gradual deprotonation of acidic groups. Pulling experiments revealed increasing adhesion of DS to the monolayer as a function of pH, presumably due both to the electrical nature of the interaction between these molecules and the progressive increase of the charge of DS with pH. Serrations exhibited by the force in pulling experiments indicate that more than a single DS molecule is stretched at the same time. In addition, pulling force remained significant even at extensions that went beyond the average contour length of a single DS molecule, which suggests the existence of a significant link between DS molecules. © 2012 American Chemical Society.